Behavioral, Physiological, and Molecular Characterization of Long-Term Administration of a Novel Estrogen Receptor Beta Agonist in a Mouse Model of Menopause - (:unkn) unknown (My University, 2021)
The menopausal loss of circulating hormones, including estrogens, is associated with negative symptoms, such as hot flashes, anxiety and depression, cognitive decline, and weight gain. Although estrogenic hormone therapies (HT) prevent many of the negative symptoms related to the menopausal transition, these same therapies are associated with increased health risks, such as the development of breast and ovarian cancers, which is mediated by the activation of the a (ERa), but not b (ERb), estrogen receptor isoform. Furthermore, ERb agonism has previously been shown to reduce preclinical indices of hot flashes, memory decline, anxiety, and depression. As most ERb agonists are only modestly selective for ERb over ERa, more selective ERb agonists are needed as potential therapeutics for menopausal women. As part of a multi-university collaboration, we have helped to develop a novel ERb agonist, EGX358, which has 750-fold selectivity for ERb over ERa without any off-target receptor activation or inhibition. Although we have shown that acute treatment with EGX358 enhances memory consolidation in young ovariectomized (OVX) mice, we have yet to investigate this novel agonist’s effects when administered long-term. In the current study, we orally treated young, OVX female mice via gavage with vehicle, the highly potent estrogen 17b-estradiol (E2), the commercially available ERb agonist diarylpropionitrile (DPN), or EGX358 for 64 days. Mice were weighed weekly and tested for vasomotor outcomes following peripheral injection with a neurokinin B agonist, anxiety- like behaviors in the open field and elevated plus maze, depression-like behaviors in the tail suspension and forced swim tests, and memory in the object placement and recognition tasks, and measured for baseline tail skin temperature at the end of the study. On the final day of treatment, mice were euthanized 30 minutes following gavage, and tissues from the dorsal hippocampus, medial prefrontal cortex, amygdala, and hypothalamus – regions highly implicated in memory, affect, and vasomotor symptoms – were collected rapidly for subsequent Western blot analyses. Mice treated with E2, DPN, and EGX358 all had reduced drug-induced increases in tail skin temperature relative to vehicle-treated mice and showed greater performance in both memory tasks than chance levels. E2 also reduced anxiety-like behaviors and baseline tail skin temperature relative to vehicle-treated mice. No other treatment effects were noted for anxiety- or depression-like behaviors, or on body weight over time. Surprisingly, there were also no treatment effects on expression or phosphorylation of proteins related to cellular activation, cellular signaling, pre- or postsynaptic strengthening, or sensitivity to glutamatergic signaling in any region examined. Additionally, there were no differences in ERb levels in the hippocampus or prefrontal cortex, suggesting that loss of sensitivity to treatment was not the reason for a lack of molecular results. Altogether, our results indicate good potential for further development of EGX358 as a new ERb-selective HT option for menopause-related symptoms, although its molecular mechanisms remain unknown.
Keywords: Anxiety; Depression; Estrogen Receptor Beta; Hot Flash; Memory; Molecular Mechanisms